(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The commonly available brick particles were impregnated with selected compounds and tested for As absorption properties. The materials tested are FeSO4 treated roasted brick particles, Fe2(SO4)3 treated roasted brick particles, FeSO4 and Na2CO3 treated brick particles, Fe2 (SO4)3 and Na2CO3 treated brick particles, ZnSO4 and Na2CO3 treated brick particles, FeSO4 and Na2HPO4 treated brick particles and waste cement plaster as such. It was observed that the substances showed different behavior of As absorption on short and long time contact. On long time contact periods the absorption capacities are much increased with high concentrations of As in solution. However with short time contact with low As concentration, the materials show saturation or no absorption after certain time period. Thus variable capacities for As absorption are shown depending on concentration, time of absorption and interval time between two contact periods. As (III) absorption was studied in the pH range 2.45-7.0. The data also show that with a contact time of 3 hrs. or more, the level of As is reduced to the acceptable limit of 0.05 ppm in water. High concentration of phosphate in water decreases as absorption as phosphate is also strongly absorbed by iron oxide impregnated brick particles. Leaching of loaded arsenic from brick particles using different common chemicals was also studied for ferrous sulfate treated roasted brick particles. Out of the solutions of common chemicals (10 % caustic soda, 20% sodium chloride, 10 % sodium carbonate, 10 % potassium dihydrogen phosphate, 10% TSP and 5 % NH3) only 10 % caustic soda can leach 95 % As from As loaded brick particles and others much less. Ordinary water within pH 4-7 leach very little arsenic from iron oxide impregnated brick particles. Bangladesh J. Sci. Ind. Res. 41(1-2), 1-14, 2006